An exploration of his thinking: Dolores Joseph Montout and the Costa Rican Caribbean, 1930-1938 - Angulo Brenes, Sonia (2024)
This article is an exploration about the thinking of a writer, thinker and Afro-Costa Rican activist Dolores Joseph Montout, especially his relation ship with the Caribbean zone. The reconstruction of his ideas is based on his journalistic work in the Thirties, in The Searchlight and The Atlantic Voice, which he assiduously wrote about his mainly concerns about the Afro-Costa Rican people. It is recovered three basic aspects of his work: a) his nationalistic inquisitiveness and his struggle for the integration and citizenship of the afro-descendant, b) his relation and controversy with the ideas of Marcus Garvey and the Universal Negro Improvement Association (UNIA) and the attacks as a consequence of his position and c) the importance that he gives to education and the intellectual background of the young people for the development of their culture, for example, through the Alpha Literary Club. As conclusions, it is evinced the contradictory and complex of his thinking and the diversity and differences among the Afro-Costa Rican people between 1930 – 1938, their nationalistic and patriotic ideas, just as the importance to continue with this kind of studies, both from the author and from other thinkers that have been made invisiblein the history of the Costa Rican Caribbean.